Investigating students’ environmental knowledge, attitude, practice and communication - Ahmad, Jamilah; Noor, Shuhaida Md; Ismail, Nurzali (Canadian Center of Science and Education, 2015)
This study investigated the relationship between students’ knowledge, attitude and practice of the environment and effective communication of environmental messages. For this purpose, a knowledge, attitude and practice (KAP) survey was conducted, involving 895 students from 16 higher learning institutions in Malaysia. The findings revealed that students in general, have a good level of environmental knowledge. However, knowledge does not necessarily lead to practice. There was a weak relationship between students’ level of knowledge and sustainable environment practices. Similarly, there was a weak relationship between students’ attitude and sustainable environment practices. Hence, attitude is not a good predictor for sustainable environment practices. These findings highlight the complexity of the relationship between students’ knowledge, attitude and sustainable environment practice. The findings of this study also suggested that, the internet is regarded as students preferred choice of media which can be utilised to disseminate environmental information. It is important, however, not to disregard the roles of more traditional media such as television and newspapers, as they can also be effectively used to deliver environmental information. Besides media, educational institutions and family also have crucial roles to disseminate environmental information and encourage good practice. Since many of the earlier studies of this nature have been conducted in at other places, particularly in the first world countries, this study is expected to contribute to the knowledge based on Malaysia’s own experience as a developing nation that aspire to champion sustainable environment